2003
DOI: 10.3354/meps260161
|View full text |Cite
|
Sign up to set email alerts
|

Composition and density of bacterial biofilms determine larval settlement of the polychaete Hydroides elegans

Abstract: Larvae of the polychaete worm Hydroides elegans settle and metamorphose in response to marine biofilms. Phylogenetic relationships among 4 marine-biofilm bacterial species identified by 16S rDNA sequences were not predictive of their inductive capacity. Two bacterial species separated by a genetic distance of 30% shared the greatest capacity for inducing metamorphosis in H. elegans. Two bacterial strains with only a 3% divergence in 16S rRNA gene sequences were very different; one strain induced metamorphosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 41 publications
11
137
2
Order By: Relevance
“…An attempt was made in the present study to determine whether bacterial species that were similar in inductive capacities are phylogenetically related, given that bacteria can be grouped by their different metabolic functions (Unabia & Hadfield 1999) as well as DNA sequence similarities (Huang & Hadfield 2003). The present study found no correlation between inductive capacities and phylogenetic relationships.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…An attempt was made in the present study to determine whether bacterial species that were similar in inductive capacities are phylogenetically related, given that bacteria can be grouped by their different metabolic functions (Unabia & Hadfield 1999) as well as DNA sequence similarities (Huang & Hadfield 2003). The present study found no correlation between inductive capacities and phylogenetic relationships.…”
Section: Discussioncontrasting
confidence: 38%
“…Previous studies have shown that specific bacterial species affect settlement in Hydroides elegans differently, and that a positive correlation exists between bacterial density and inductive capacity (Huang & Hadfield 2003). In the present study, there was only a positive correlation when the density was increased for the strongly inductive bacterium Pseudoalteromonas luteoviolacea, but not for the 3 other tested species (Alteromonas alvinellae, Vibrio harveyi, and Bacillus firmus) that were moderately or weakly inductive.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…The EMPB provides food for many grazing invertebrates (such as gastropods and amphipods; e.g. Underwood 1978, Christofoletti et al 2011, Sanz-Lázaro et al 2015 and facilitates the settlement of algal propagules and invertebrate larvae (O'Connor & Richardson 1998, Huang & Hadfield 2003. In addition, relatively recent studies have shown that some invertebrates (namely littorinids and barnacles) can in turn positively affect EMPB biomass through facilitation mechanisms (Skov et al 2010, suggesting that interaction webs involving EMPB are complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent experiments have shown that biofilms do not facilitate settlement of all macroorganisms. This has been demonstrated in a variety of marine organisms such as barnacles, oysters, and Ulva [25] fed by bacteria [56] and diatoms [57]. Because of competition for nutrients and light, it is believed that microorganisms produce metabolites to repel specific macroorganisms [58].…”
Section: Macro-organism Adhesionmentioning
confidence: 99%